Pengaruh Green Accounting Dan Good Corporate Governance Terhadap Kinerja Keuangan - Huda Fadillah; Tri Utami (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2026)
This study aims to analyze the effect of Green Accounting and Good Corporate Governance on Financial Performance. This type of research is quantitative. The study population is the Kompas 100 Index companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The sampling technique used is Purposive Sampling technique. Hypothesis testing uses panel data regression with the help of eviews 12 statistical tools. The results of the study indicate that Green Accounting and the Audit Committee have an influence on Financial Performance. Independent Commissioners, Institutional Ownership and the Board of Directors have no influence on Financial Performance.